Mid-infrared supercontinuum generation in tapered As2S3 chalcogenide planar waveguide. Issue 19 (27th October 2016) - Zhang, Xiang; Hu, Hongyu; Li, Wenbo; Dutta, Niloy K.
Abstract: We numerically demonstrate mid-infrared supercontinuum generation in a non-uniformly tapered chalcogenide planar waveguide. This planar rib waveguide of As2 S3 glass on MgF2 is 2 cm long with increasing etch depth longitudinally to manage the total dispersion. This waveguide has zero dispersion at two wavelengths. The dispersion profile varies along the propagation distance, leading to continuous modification of the phase-matching condition for dispersive wave emission and enhancement of energy transfer efficiency between solitons and dispersive waves. Numerical simulations are conducted for secant input pulses at a wavelength of 1.55 μm with a width of 50 fs and peak power of 2 kW. Results show this proposed scheme significantly broadens the generated continuum, extending from 1 to 7 μm.